Euskaldunek euskalkienganako izan dituzten jarrerez - Zuazo, Koldo (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1987)
The aim of this essay is to gather together all accounts of the attitudes of the speakers of Basque (euskaldunes) towards the various varieties of the Basque language. An analysis of the data allows us to assert that since the beginning of the 18th century, two of these varieties have been favoured by the euskaldunes: the Beterri variety, from Gipuzkoa, and the so-called ’Kostatar’ from Lapurdi. To mention but one of the most important consequences of this fact for the current state of the language, it gives a solid grounding to the proposals of those who argued that the central varieties should be used as a model for a standardised language. We also point out the negative attitudes held by Basque speakers towards certain varieties, and particularly that of Bizkaia; this will doubtless be one of the main issues to be resolved during the process of the normalisation of Basque.